Dermoscopic and histopathological correlation in macular hyperpigmented facial lesions - Mülayim, Kamil; Yücel, Aydın (Journal of Surgery and Medicine, 2022)
Background/Aim: Solar lentigo, seborrheic keratosis, actinic keratosis, lentigo maligna are confusable hyperpigmented lesions. Dermoscopy is an important tool to distinguish the pigmented lesions on the face. This study aimed to determine the reliability of dermoscopy by comparatively analyzing dermoscopic findings with the histopathologic examination of facial hyperpigmented flat lesions. Methods: Patients with hyperpigmented flat lesions on the face such as solar lentigo, seborrheic keratosis, and actinic keratosis were included in this retrospective cohort study. Those with other causes of facial hyperpigmentation were excluded from the study, based on history, clinical evaluation, Wood’s lamp examination, and dermoscopic findings. The dermoscopic criteria form, prepared for solar lentigo, seborrheic keratosis, actinic keratosis, and lentigo maligna were filled out. Biopsy was taken for histopathologic evaluation. Results: Fifty-one patients, 26 males, and 25 females, with 53 skin lesions were evaluated. We did not statistically evaluate 3 lesions that had a histopathologic diagnosis of actinic keratosis + solar lentigo. The other 50 lesions’ histopathologic diagnoses were actinic keratosis in 32 lesions, seborrheic keratosis in 9, and solar lentigo in 9. Kappa test was used for statistical analysis, which revealed a value of 0.645 (P<0.001). This shows that the dermoscopic and histopathological diagnoses of the hyperpigmented flat lesions on the face were moderately compatible. Conclusion: Since the dermoscopic diagnosis of facial pigmented lesions cannot be based on the presence of one criterion, we deduce that histopathology is still the gold standard for accurate diagnosis.